Study on Ti2AlC/Mg Matrix Composites with Dual-scale Three-dimensional Network - Chen, Yujia; Hu, Lai (Manufacturing Technology Journal, 2022)
The development of metal structural materials with low density, high specific strength and large internal friction is extremely urgent for the development of lightweight, high speed and high power of equipment and railway. The properties, microstructure and the evolution of interfacial bonding of composite materials are closely related. In this paper, the microstructure of Ti2AlC/Mg matrix composites with double-scale three-dimensional network is mainly studied. The prepared composite material presents a three-dimensional network in macro-micro scale, and the matrix and reinforcement are connected with each other. The mechanical properties and damping properties of the prepared dual-scale three-dimensional network Ti2AlC/Mg matrix composites and magnesium alloy matrix were tested. At the same time, the equivalent modulus of three-dimensional network Ti2AlC/Mg matrix composites on microscopic scale is predicted by finite element method according to the basic properties of Ti2AlC ceramics and AZ91D. The following conclusions are drawn: the ultimate bending strength of the composite material is increased by about 10% compared with its matrix magnesium alloy, and its ability to maintain strength is greatly improved compared with the matrix. Using the extracted information, the equivalent modulus of the composite microscopic model is calculated to be 31.25734 GPa, which is consistent with the experimental results. It provides data and theoretical support for similar research.
Keywords: Double scale; Three-dimensional network; Ti2AlC/Mg matrix composites; Magnesium alloy; Comprehensive performance